Oral History and Reminiscence Therapy: Preserving Elderly Narratives at Wisma Harapan Asri in Semarang City - Baihaqi, Ahmad Fauzan; Sembiring M, Bryna Rizkinta; Rizal, Aslama Nanda; Satrio, Imam; Shadday, Faulla; Annu, Alfarel Rafi Annu (Yayasan Rahmat Islamiyah, 2025)
This article discusses the integration of oral history and memory therapy as a community service approach for elderly people at the Harapan Asri Nursing Home in Semarang, Central Java. The project was carried out by the History Department of Diponegoro University in 2025, with the aim of preserving local wisdom and empowering elderly people through the documentation of their personal narratives. Using participatory methods, the team conducted in-depth interviews with the elderly, focusing on their memories and experiences related to social changes in Semarang over the past half-century. The case study of Mr Irwan, a 79-year-old resident of Chinese descent, provides valuable insights into the challenges faced by minority communities during periods of political turmoil. The memory sessions not only served as a source of oral history but also provided psychological benefits for the elderly participants, helping them to restructure their identities and foster a sense of pride in their life journeys. This article highlights the potential of oral history as a tool for social and emotional empowerment, as well as its role in enriching local historical narratives. Our conclusion is that it is necessary to integrate psychological and sociological perspectives into the oral history framework to understand the complex experiences of marginalised individuals and communities. This study demonstrates the value of an interdisciplinary approach in community service initiatives and emphasises the importance of preserving the collective memory of the elderly.